2016
DOI: 10.1111/iej.12704
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal root fractures in posterior teeth without dental trauma: tooth/root distribution and clinical characteristics

Abstract: HRF in posterior teeth without dental trauma occurred mainly in patients aged between 50 and 70, in nonendodontically treated teeth, teeth with attrition but without crown and bridge restorations, maxillary molars and with periodontal and periapical bony destruction. Periodontal condition, occlusal wear and patients' age at diagnosis were the possible related factors. HRF in posterior teeth without dental trauma is a diagnostic challenge and even misdiagnosed. A thorough clinical examination, radiographic anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
2
1
0
Order By: Relevance
“…In the present study, 50 high-resolution CBCT scans were assessed in patients with a diagnosis of tooth fracture. The results showed that the type of fracture is not related to the type of retention used, which coincides with the results reported by Tsai et al ( 24 ) where the presence of a post was not closely related to the presence of horizontal or vertical root fractures in posterior teeth ( 25 ). These results contrast with those reported by Maddalone et al ( 21 ) in a prevalence study showing an increased risk of vertical root fracture (VRF) in teeth restored with a post; these authors found a statistically significant difference in relation to teeth without a post.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, 50 high-resolution CBCT scans were assessed in patients with a diagnosis of tooth fracture. The results showed that the type of fracture is not related to the type of retention used, which coincides with the results reported by Tsai et al ( 24 ) where the presence of a post was not closely related to the presence of horizontal or vertical root fractures in posterior teeth ( 25 ). These results contrast with those reported by Maddalone et al ( 21 ) in a prevalence study showing an increased risk of vertical root fracture (VRF) in teeth restored with a post; these authors found a statistically significant difference in relation to teeth without a post.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, 50 high-resolution CBCT scans were assessed in patients with a diagnosis of tooth fracture. The results showed that the type of fracture is not related to the type of retention used, which coincides with the results reported by Tsai et al [24] where the presence of a post was not closely related to the presence of horizontal or vertical root fractures in posterior teeth [25].…”
Section: Discussionsupporting
confidence: 90%
“…HRF presents a diagnostic and treatment challenge for the endodontist 3 . Clinically, root fracture can present as a mobile, extruded or displaced segment, but the definitive diagnosis requires appropriate radiographic examination 4 .…”
Section: Introductionmentioning
confidence: 99%